Spiritual companyn : strategies to improve the quality of work of life for outsourced employees in aerofood catering service - Achmad Sholihin (Enrichment : Journal of Management, 2023)
Outsourced employees as workers do not have competency guarantees, so that various unfavorable conditions may affect work behavior. The strategy of spirituality absorbed in work behavior is seen as effective in supporting the company's vision. The purpose of this research is to analyze the spirituality strategy that is integrated as a strategy to improve the quality of work of life of outsourced employees. This research method used a survey method with a total sample of 124 outsourced employees at PT Aerofood Aerowisata Catering Service (ACS). Data were collected through questionnaires and a Likert scale, and data were analyzed using non-parametric bivariate statistics. The results of Kendall's tau_b correlation obtained a coefficient value of 0.812 at p = 0.000 (p <0.05) proving that there is a positive correlation between the implementation of the company's spiritual strategy and the quality of employee work life; and the Spearman rho test obtained a value of rxy = 0.846 at p = 0.000 (p <0.05) proving the existence of a company's spiritual integrity with the quality of employee work life. The existence of integrity between spirituality and quality of work of life reaches 71.6%, which means that the two variables have a relatively high close relationship.